Autoantibodies and SARS-CoV-2 infection: A case report - T. I. Kalenchic; S. L. Kabak; I. V. Korenevskaya (Научно-практическая ревматология, 2022)
The article describes a COVID-19 patient with several biomarkers of systemic cytokine storm (including multiple excess over the reference values of C-reactive protein, ferritin and D-dimer) and increased level of autoantibodies (aPL and anti-CCP). At the same time contrast-enhanced CT and US failed to detect pulmonary embolism or lower limb deep vein thrombosis. Three months after discharge from the hospital, a high level of antiphospholipid antibodies and D-dimer remained. The relationship between infection with SARS-CoV-2 and autoimmunity has been discussed.